The character concept in evolutionary biology - Wagner, Gunter P. (Academic Press, 2001)
Almost all evolutionary biologists, indeed all biologists, use particular features to study life. These characteristics or features used by evolutionary biologists are used in a particular way to unravel a tangled evolutionary history, document the rate of evolutionary change, or as evidence of biodiversity. "Characters" are the "data" of evolutionary biology and they can be employed differently in research providing both opportunities and limitations. The Character Concept in Evolutionary Biology is about characters, their use, how different sorts of characters are limited, and what are appropriate methods for character analysis. Leading evolutionary biologists from around the world are contributors to this authoritative review of the "character concept." Because characters and the conception of characters are central to all studies of evolution, and because evolution is the central organizing principle of biology, this book will appeal to a wide cross-section of biologists. Key Features * Focuses upon "characters"--Fundamental data for evolutionary biology * Covers the myriad ways in which characters are defined, described, and distinguished * Includes historical, morphological, molecular, behavioral, and philosophical perspectives